2020
DOI: 10.1556/2006.2020.00067
|View full text |Cite
|
Sign up to set email alerts
|

Using deliberate mind-wandering to escape negative mood states: Implications for gambling to escape

Abstract: Background and aims: Slot machines are a pervasive form of gambling in North America. Some gamblers describe entering “the slot machine zone”—a complete immersion into slots play to the exclusion of all else. Methods: We assessed 111 gamblers for mindfulness (using the Mindful Attention Awareness Scale (MAAS)), gambling problems (using the Problem Gambling Severity Index (PGSI)), depressive symptoms (using the Depression, Anxiety, and Stress Scale), and boredom proneness (using the Boredom Proneness Scale). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
(66 reference statements)
3
7
0
Order By: Relevance
“…Our findings regarding the relationship between MW and anxiety and depressive symptoms are similar to our previous results with adolescents (Figueiredo et al, 2020). Those from Kruger et al, 2020 highlighted the important role of depressive and anxiety symptoms for excessive MW.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings regarding the relationship between MW and anxiety and depressive symptoms are similar to our previous results with adolescents (Figueiredo et al, 2020). Those from Kruger et al, 2020 highlighted the important role of depressive and anxiety symptoms for excessive MW.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have shown significant correlations between slot machine zone experiences and positive affect [47,52], indicating that zoning is subjectively pleasant. Other work has shown positive relationships with depression symptomatology [21, 52; but see 56], including relationships between problem gambling, depression, the slot machine zone, and lower rates of mindful attention outside of gambling [46,52,57]. Consistent with the influential Pathways Model of problem gambling [60], these findings collectively suggest that positively reinforcing gambling events (i.e.…”
Section: Individual Traits That Impact the Zonesupporting
confidence: 65%
“…Note: The two dominant constructs for understanding the slot machine zone (Csikszentmihalyi's Flow Theory, and dissociation from Jacobs' General Theory of Addictions), appear at odds with respect to whether the experience is positive, benign, harmful, or pathological. Dark flow is a variant on flow theory that refers specifically to negative consequences that incidentally occur during prolonged gambling in a flow state [21,52,54,57] 'positive' dissociative phenomena during gambling remains unclear. The Dissociative Experiences Scale (DES), which includes a greater number of items specific to depersonalization and derealization and queries dissociative experiences in all areas of participants' lives [72], has been positively associated with Gamblers' DQ ratings [19,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recording of psychophysiological measures during gambling may provide a window into the psychological processes involved in gambling (e.g., positive reinforcement, excitement) and may further uncover individual differences relevant to the risk of experiencing gambling-related harms. Beginning in the 1980s (e.g., [ 8 ]), a range of physiological measures have been examined in relation to gambling, including various cardiographic indices [ 9 12 ], electrodermal indices [ 13 16 ], muscular indices [ 17 19 ], and body temperature [ 20 ]. Some of these measures have been further linked to problem gambling status, although not consistently so [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%